Conformational changes to zein and its binding interactions with sodium caseinate during the pH-driven self-assembly using multi-spectroscopic and hydrostatic methods. (March 2023) - Wang, Lei; Rose, Devin; Li, Keting; Chen, Xingyi; He, Laping
Abstract: Stable zein-based nanocomplexes with sodium caseinate (NaCas) could be formed using a pH-cycle treatment without organic solvents, but structural changes of water-insoluble zein was not clearly studied. The objective of this work was to investigate the conformational changes of zein and its binding with NaCas using 8-anilinonaphthalene-1-sulfonate (ANS) as a probe that could exclusively bind to zein. Extrinsic fluorescence and three-dimensional fluorescence spectroscopy showed the acidification induced the zein re-folding, as revealed by the increased polarity around tyrosine/tryptophan residues. The UV–Vis spectroscopy and morphological observations in scanning/transmission electron microscopy as well as the goniometer further confirmed these changes. The Raman spectroscopy and increased contents of sulfhydryl groups indicated that the interactions between zein and NaCas were favored by a combination of hydrophobic interaction and disulfide/hydrogen bonds. Information derived from this work could help rationalize the design of zein-NaCas nanocomplex for encapsulation, protection, and release of bioactives using pH-cycle treatment. Graphical abstract: Image 1 Highlights: Conformational changes to zein and its interaction with NaCas during pH-cycle process were studied. ANS quenched the intrinsic fluorescence of zein dissolved at pH 11.5 by forming ground state complex. The microenvironment of amino acid residues and conformation of zein were changed upon pH acidification. The interactions of pH-cycle process were driven by a combination of hydrogen bond and hydrophobic forces. Morphology indicated by SEM/TEM and surface tension was significantly altered during the pH-cycle treatment.